Secure License Management for Interoperable DRM Systems - Serrão, C.; Delgado, J.; Dias, J. (Proceedings of the IADIS International Conference Information Systems (ICIS2008), Algarve, Portuga, 2008)
To protect the digital Intellectual Property in the current digital World is proving to be a hard task. Not only it is complex to provide robust and reliable mechanisms capable of preventing the unauthorized content copying and utilization, but also it is complex to provide a mechanism for specifying and enforcing how content can and will be used. Rights Expression Languages (REL) allows content providers and distributors to syntactically and semantically express a set of rights that are associated to a digital object. In this paper we provide a model for the definition and description of the digital object license granting rights life cycle management and the processes necessary to secure the license throughout this entire life cycle.